Matematică
hjdjfjdj
9

2x+4(x-1)=5x 6-3(1-x)+2(x-5)=3 3(2x+1)-5(x+2)=3x-4 2x+4x(1-x)=2+2(2x+5) 5x-4(2x+3)=3-2(4-5x) 4x+2(3x-1)=1+3(x-1) 7(x+1)=3(x-2)-4(5-x)

+0
(1) Răspunsuri
dyenutzaranete

2x+4(x-1)=5x 2x+4x-4=5x 6x-5x=4 x=4 6-3(1-x)+2(x-5)=3 6-3+3x+2x-10=3 5x=3+7 x=10/5 x=2 3(2x+1)-5(x+2)=3x-4 6x+3-5x-10=3x-4 x-3x=7-4 -2x=3 x=-3/2 2x+4x(1-x)=2+2(2x+5) 2x+4x-4x²=2+4x+10 -4x²+6x-4x=12 -4x²+2x=12 2x(1-2x)=12 2x=12     x=12/2=6      1-2x=12     -2x=12-1      -x=11/2     x=11/2 5x-4(2x+3)=3-2(4-5x) 5x-8x-12=3-8+10x -3x-10x=-5+12 -13x=7 x=-7/13 4x+2(3x-1)=1+3(x-1) 4x+6x-2=1+3x-3 10x-3x=-2+2 7x=0 x=0/7 x=0 7(x+1)=3(x-2)-4(5-x) 7x+7=3x-6-20+4x 7x-7x=-26-7 0x=-33 x=-33/0 x=0

Adaugă răspuns